A New DSP-Based Physical Layer Encryption Technique Applied to Passive Optical Networks - Francisco Abbade, Marcelo Luis [UNESP]; Lessa, Leonardo Silva [UNESP]; Santos, Melissa de Oliveira [UNESP]; Prado, Afonso Jose do [UNESP]; Aldaya, Ivan [UNESP]; Jaworski, M.; Marciniak, M. (Ieee, 2018)
Point-to-multipoint architecture poses serious security problems to passive optical networks (PONs). In this paper, we propose the use of a new digital signal processing (DSP)-based technique to improve the confidentiality of signals traveling through PONs. The technique consists of phase-shifting and delaying the spectral components of baseband signals that further modulate optical carriers. Our simulation analysis encompasses the application of the technique to binary phase-shift keying (BPSK) in an intensity modulated-direct detection (IM-DD) system. Results reveal that the encrypted signals may be properly decoded even when 64 PON users are considered and suggest the potential of the proposed technique for practical implementations. From a security point of view, we show that the proposed technique utterly outperforms the Advanced Encryption Standard (AES) in brute force attacks.
Keywords: physical layer security; digital signal processing; passive optical networks